Biochemical and transcriptional analyses of cadmium-induced mitochondrial dysfunction and oxidative stress in human osteoblasts. Issue 15 (3rd August 2018) - Monteiro, Cristina; Ferreira de Oliveira, José Miguel P.; Pinho, Francisco; Bastos, Verónica; Oliveira, Helena; Peixoto, Francisco; Santos, Conceição
ABSTRACT: Cadmium (Cd) accumulation is known to occur predominantly in kidney and liver; however, low-level long-term exposure to Cd may also result in bone damage. Few studies have addressed Cd-induced toxicity in osteoblasts, particularly upon cell mitochondrial energy processing and putative associations with oxidative stress in bone. To assess the influence of Cd treatment on mitochondrial function and oxidative status in osteoblast cells, human MG-63 cells were treated with Cd (up to 65 μM) for 24 or 48 h. Intracellular reactive oxygen species (ROS), lipid and protein oxidation and antioxidant defense mechanisms such as total antioxidant activity (TAA) and gene expression of antioxidant enzymes were analyzed. In addition, Cd-induced effects on mitochondrial function were assessed by analyzing the activity of enzymes involved in mitochondrial respiration, membrane potential (ΔΨm), mitochondrial morphology and adenylate energy charge. Treatment with Cd increased oxidative stress, concomitantly with lipid and protein oxidation. Real-time polymerase chain reaction (qRT-PCR) analyses of antioxidant genes catalase ( CAT ), glutathione peroxidase 1 (GPX1 ), glutathione S-reductase ( GSR ), and superoxide dismutase (SOD1 and SOD2) exhibited a trend toward decrease in transcripts in Cd-stressed cells, particularly a downregulation of GSR. Longer treatment with Cd (48 h) resulted in energy charge states significantly below those commonly observed in living cells. Mitochondrial function was affected by ΔΨm reduction. Inhibition of mitochondrial respiratory chain enzymes and citrate synthase also occurred following Cd treatment. In conclusion, Cd induced mitochondrial dysfunction which appeared to be associated with oxidative stress in human osteoblasts.